2010
DOI: 10.1016/j.neulet.2010.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the sesquiterpene (−)-α-bisabolol as a novel peripheral nervous blocker

Abstract: Essential oils are natural, complex and multi-component systems composed mainly of terpenes in addition to some other non-terpenes compounds that are widely used to prevent and treat human diseases. (-)-alpha-Bisabolol is an unsaturated monocyclic sesquiterpene alcohol found as the major constituent of many essential oils, like the German chamomile (Chamomilla recutita (L.) Rauschert), a plant reported to reduce the perception of acute pain and used for centuries for their medicinal properties. Recently, our g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…These molecules freely cross cellular membranes and may serve various signaling roles inside the cell. In addition, there are some reports indicating that essential oil plant components are active towards ion channels and receptors (Gonçalves et al, 2008;de Almeida et al, 2008;Alves et al, 2010). Apart from rational drug design and novel synthetic efforts, natural products are still been investigated for novel chemical structures that may interact with known and unknown pharmacological targets.…”
Section: Essential Oils: New Source For New Moleculesmentioning
confidence: 99%
“…These molecules freely cross cellular membranes and may serve various signaling roles inside the cell. In addition, there are some reports indicating that essential oil plant components are active towards ion channels and receptors (Gonçalves et al, 2008;de Almeida et al, 2008;Alves et al, 2010). Apart from rational drug design and novel synthetic efforts, natural products are still been investigated for novel chemical structures that may interact with known and unknown pharmacological targets.…”
Section: Essential Oils: New Source For New Moleculesmentioning
confidence: 99%
“…Some activities have been associated with (−)-α-bisabolol such as anti-mutagenic capability (Gomes-Careneiro et al), pro-apoptotic capability in models of primary human acute leukaemia cells (Cavaliere et al) and the capacity to decrease nervous excitability supposedly associated with an irreversible blockade of voltage-dependent sodium channels (Alves et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Visceral afferents express a wide range of membrane receptors (including vanilloid receptors, TRPV1) to chemical stimuli, which are involved in sensory signaling from the gut to the central nervous system 11 . This antinociceptive effect may be related to the high bisabolol content in EOVA, since that Alves et al 12 have just reported that bisabolol is able to reduce the neuronal excitability in a concentration--dependent manner.…”
Section: Discussionmentioning
confidence: 96%